2008
DOI: 10.1016/j.ejcts.2008.07.066
|View full text |Cite
|
Sign up to set email alerts
|

Human adaptation to ischemia by preconditioning or unstable angina: involvement of nuclear factor kappa B, but not hypoxia-inducible factor 1 alpha in the heart

Abstract: Cardiac function was improved by ischemic preconditioning in both stable and unstable patients. Unstable angina per se had no effect. NFkappaB-regulated genes were influenced by ischemic preconditioning, but hypoxia-inducible genes were not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…According to the results of the study by Kawata et al, HIF-1α does not involve in VEGF upregulation in ischemic preconditioning pathway [37] . Furthermore, NF-κB regulated genes were influenced by ischemic preconditioning but hypoxia inducible genes were not in the patients with angina, undergoing coronary artery bypass grafting [38] . Ischemic postconditioning is a cardioprotective modality against reperfusion injury through series of brief reflow interruptions applied at the very onset of reperfusion [39] .…”
Section: Involvement Of Hif-1 In Ischemic Preconditioning and Post Comentioning
confidence: 99%
“…According to the results of the study by Kawata et al, HIF-1α does not involve in VEGF upregulation in ischemic preconditioning pathway [37] . Furthermore, NF-κB regulated genes were influenced by ischemic preconditioning but hypoxia inducible genes were not in the patients with angina, undergoing coronary artery bypass grafting [38] . Ischemic postconditioning is a cardioprotective modality against reperfusion injury through series of brief reflow interruptions applied at the very onset of reperfusion [39] .…”
Section: Involvement Of Hif-1 In Ischemic Preconditioning and Post Comentioning
confidence: 99%
“…Several cycles of ischemia followed by short episodes of reperfusion signifi cantly reduced the infarct size after a subsequent myocardial ischemia. Very recent studies with patients suffering from cardiac angina corroborate these experimental data, that injury-induced ischemic events protect these patients from severe myocardial infarction [ 91 ]. Ischemic preconditioning is not confi ned to the heart.…”
Section: Tissue Protection By Hypoxic Preconditioningmentioning
confidence: 69%
“…NF-κB exerts a critical effect on regulating cardiomyocyte apoptosis, especially in response to oxidative stress following myocardial infarction (Imam et al, 2018). In human, Czibik et al (2008) reported that NF-κB nuclear translocation was reduced at reperfusion in stable angina patients after ischemic precondition. However, researchers have not conclusively determined whether it exerts cardioprotective effects or deleterious effects.…”
Section: Nuclear Factor-κbmentioning
confidence: 99%